Phenomenology related to the kinetics of Kolbe electrosynthesis - Cerviño, R. M. (1984)
The Kolbe electrosynthesis on polycrystalline platinum in 1 M acetic acid/1 M potassium acetate electrolyte at 30 ° C was studied by using potentiostatic, low-frequency potentiodynamic and impedance techniques. Reaction products and their distribution as a function of potential were determined. There is a good correspondence in the potential ranges where changes in both stationary and non-stationary kinetic data, electrode resistance, electrode capacitance and reaction products were found. Results confirm the existence of different electrochemical reactions and correspondingly different reaction intermediates in the various Tafel regions.